Gender equality, norms and practices: Post-script to special issue on new actors, old donors and gender equality norms in international development cooperation. (July 2018) - Barnett, Michael
The contributions raise several important issues regarding the norm of gender equality in development organizations, and I want to raise the following points for further consideration. Does it matter if we treat gender equality as a norm or practice? The articles suggest that there is general movement toward the norm, but what it means to do gender equality is quite fractured. Who decides what gender equality means? Why do organizations feel the need to adopt this norm? Organizations have different motives, and these motives are probably important for understanding whether these norms have any impact. Impact refers to effects, and there are various kinds of effects raised by the articles, though focused mainly on the norm's institutionalization rather than its impact.